2003
DOI: 10.1182/blood-2002-06-1623
|View full text |Cite
|
Sign up to set email alerts
|

A promoter mutation in the erythroid-specific 5-aminolevulinate synthase (ALAS2) gene causes X-linked sideroblastic anemia

Abstract: X-linked sideroblastic anemia (XLSA) is caused by mutations in the erythroidspecific 5-aminolevulinate synthase gene (ALAS2). XLSA was diagnosed in a 32-year-old woman with a mild phenotype and moderately late onset. Pyridoxine therapy had no effect in the proband, but in her affected son engendered a modest increase in hemoglobin concentration and a 4-fold reduction in ferritin iron. Molecular analysis identified a C to G transversion at nucleotide ؊206 from the transcription start site, as defined by primer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…31 In this context, it has been reported that the deleted region contained a functionally important element for ALAS2 transcription. 16 Bekri et al reported a C-to-G transversion at nucleotide -206 (c.-258C>G) from the transcription start site in the proximal region of the human ALAS2 gene in patients with XLSA; 24 however, May et al identified this transversion in normal individuals from South Wales at the rate of 0.05, suggesting that this promoter mutation is a polymorphism. 32 In conclusion, we have identified a novel erythroid-specific enhancer in the first intron of the human ALAS2 gene, the enhancer function of which may be directed by GATA1 with other transcription factors, such as EKLF and AP-1 binding proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 In this context, it has been reported that the deleted region contained a functionally important element for ALAS2 transcription. 16 Bekri et al reported a C-to-G transversion at nucleotide -206 (c.-258C>G) from the transcription start site in the proximal region of the human ALAS2 gene in patients with XLSA; 24 however, May et al identified this transversion in normal individuals from South Wales at the rate of 0.05, suggesting that this promoter mutation is a polymorphism. 32 In conclusion, we have identified a novel erythroid-specific enhancer in the first intron of the human ALAS2 gene, the enhancer function of which may be directed by GATA1 with other transcription factors, such as EKLF and AP-1 binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The human ALAS2 proximal promoter region (g.4820_5115, between -267 and +29 from the transcription start site) 16,24 was cloned into the multiple-cloning site of pGL3basic [referred to as pGL3-AEpro (-267)]. A single DNA fragment (5.2 kbp), carrying the ALAS2 proximal promoter, first exon, first intron and the untranslated region of the second exon, was subcloned into the multiple cloning site of pGL3basic [referred to as pGL3-AEpro(-267)+intron1].…”
Section: Promoter/enhancer Activity Assaysmentioning
confidence: 99%
“…Characterization of the promoter region of the human ALAS2 gene revealed several putative binding sites for the ery- throid-specific transcription factors GATA-1 and NF-E2. In addition, as discussed before, the IRE motif of ALAS2 mRNA in the 5´-protein noncoding region is involved in regulating the translation of mRNA to protein (Bekri et al 2003). Mice lacking ALAS2 died in the embryonic stage (Nakajima et al 1999).…”
Section: Biosynthesis and Regulation Of Heme Metabolism In Mitochondriamentioning
confidence: 99%
“…In disorders of heme biosynthesis including anemia with ALAS2-deficient, ring-sideroblasts and hemosiderin characteristics of iron accumulation appear (May and Bishop 1998;Bekri et al 2003). These phenotypes are distinguished from iron-deficient anemia.…”
Section: Functions and Regulation Of Iron Metabolism In Mitochondriamentioning
confidence: 99%
“…f Variants with a frequency o1% are de¢ned as rare. mutations cannot be excluded since null mutations in promoters have already been reported in other diseases [Bekri et al, 2003]. Regulatory variants, defined as variants upstream of the start codon, including the 5 0 region, 5 0 UTR and intron 1, and variants in the 3 0 UTR, were reported.…”
Section: Variants With Unclear Pathogenic Signi¢cancementioning
confidence: 99%